Growth and stem quality of hardwood trees planted 18–29 years ago on abandoned farmland following recommended silvicultural practices - Alain Cogliastro; Daniel Gagnon (The Forestry Chronicle, 2019)
The objective of this study is to provide an account of the growth results of valuable hardwood plantations several decades old which have received silvicultural treatments recommended for planting hardwoods on abandoned farmland. Diameter growth and stem quality of sugar maple (Acer saccharum Marsh.), black walnut (Juglans nigra L.), bur oak (Quercus macrocarpa Michx.) and red oak (Quercus rubra L.) are analysed. Data were from 15 plantations located in south-western Quebec. The mean annual diameter increments were highest for red oak (0.83 cm yr-1) and black walnut (0.75 cm yr-1), and lowest for bur oak (0.55 cm yr-1) and sugar maple (0.51 cm yr-1). These values are comparable to, or exceed, the best rates in the literature. A mean proportion of 78% to 95% of the first log without defects were produced, depending on the species. Tree mean densities (640 trees/ha) will allow a selection of better stems by thinning. Elite trees have diameters that are 17% to 23% above the average. These results lead us to believe in the potential for the production of quality hardwood timber in plantations in Québec.